Norway : 2017 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights that the Norwegian economy is slowly recovering from the oil shock as domestic demand grew stronger aided by accommodative macroeconomic policies. Inflation declined recently owing to the pass-through of krone appreciation, but expectations remain well-anchored. In addition, banks remain profitable and well capitalized. Mainland growth is projected to increase from just below 1 percent in 2016 to 1.75 and 2.25 percent in 2017 and 2018 respectively, supported by the recovery of exports and stronger private demand. Inflation is projected to edge down further in pace with the unwinding of krone depreciation, before converging to the target over the medium term as trading-partner inflation rises.